Sonographic Assessment of Fetal Cephalic Index among the Population of Western UP: A Prospective Observational Study - Nandkishor Gupta; Neeshu Bala; Nitya Nand Srivastava; Kailash Mittal (JCDR Research and Publications Pvt. Ltd., 2020)
Introduction: Cephalic Index (CI) also called as cranial index is the ratio of the maximum breadth to maximum length of head. Aim: To assess the shape of skull according to the CI and to identify factors affecting the CI estimation like gestational age, weight of fetus, maximum breadth of fetal heads and maximum length of fetal heads in the Etawah Region (UP) in India. Materials and Methods: The present prospective observational study was performed on the pregnant ladies. These ladies were enrolled for the study when they visited the Radio-diagnosis Department of Uttar Pradesh Medical University Hospital, Saifai, Etawah for Ultrasound (USG). A total number of 550 ultrasound images were collected for study. The measurement of Maximum Breadth of Fetal Heads (BPD i.e., Biparietal Diameter) and Maximum Length of Fetal Heads (APD i.e., Antero-Posterior Diameter) were taken on USG machine, recorded for analysis. When associating the measures of precision for different subgroups, oneway ANOVA analysis of variance was used for the modest and efficient errors. Multivariate logistic regression analysis was used to identify factors affecting the CI estimation like gestational age, weight of fetus, maximum breadth of fetal heads and maximum length of fetal heads. Results: Out of 550 studied fetus, majority 222 (40.4%) of the fetus were belonging to the gestational age group 30- 35 weeks. Weight of fetus, maximum breadth of fetal heads, and maximum length of fetal heads in different gestational age were statistically significant; but CI was statistically insignificant. Pearson correlation between the gestational age, weight of fetus, maximum breadth of fetal heads, maximum length of fetal heads and CI was determined and correlation was statistically significant with each other's; but statistically insignificant correlation was observed between maximum length of fetal heads and CI. Conclusion: Mesocephaly is the dominant head shape among the western part of UP (India) particularly in Etawah and Mainpuri region which was of CI range from 75 to 79.9.